The given expression can be simplified to: 3b-a
When simplified it is: 2a+8b+4
p=b+3a+c p-3a-c=b+3a-3a+c-c p-3a-c=b b=p-3a-c
5ab-2ab+4a-b+5b = 3ab+4a+4b
a+a+a+a+b+b - add the like terms =4a+2b 4a and 2b cannot be added because they are not like terms.
3(a + b) + a = 3a + 3b + a = 4a + 3b
a-b+a-b+2b+a = 4a
If a + b = 6, what is the value of 3a + 3b?
(2a - b)(2a + b)
This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)
3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)
4a + 3c - 2b - c + a - b = 5a - 3b + 2c
It is simply as stated in the question. Without information about a or b, the expression cannot be simplified nor evaluated.
The expression is: (4a+b)/(2a-5b)
= a + b - 2
Clearly, there are some signs missing. So let's try the four possibilities for the second terms: 1. + and + 3a + 4b = 7a + 4b Subtract 4b from each side: 3a = 7a Subtract 3a from each side: 0 = 4a Answer : a = 0, b indeterminate (ie can have any vaue). 2. + and - 3a + 4b = 7a - 4b Subtract 4b from each side: 3a = 7a - 8b Subtract 7a from each side: -4a = -8b or 4a = 8b Answer: a = 2b 3. - and - 3a - 4b = 7a - 4b Add 4b to each side: 3a = 7a Subtract 3a from each side: 0 = 4a Answer : a = 0, b indeterminate (ie can have any vaue). 4. - and + 3a - 4b = 7a + 4b Add 4b to each side: 3a = 7a + 8b Subtract 7a from each side: -4a = 8b or 4a = -8b Answer: a = -2b Can't do better than that with the information available.
(a + 2 - b) (a + 2 + b)
-2a plus 3b
3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)